Prognostic factors for malignant pleural mesothelioma - Brims, Fraser; Maskell, N. (2013)
The prognosis for patients with malignant pleural mesothelioma (MPM) is generally regarded as poor, although rare cases of long-term survivors are recognised. Previous prognostic scoring systems have been based on clinical trial populations and are not widely utilised. Population studies consistently confirm non-epithelioid histology, advanced age, and male gender as independent risk factors for poor outcome of MPM. Genetic and immunohistochemical studies continue to provide advances in tumour biology, but no clear validated prognostic factors have been identified to date. Nuclear mitotic and atypia grading systems may provide useful prognostic knowledge; further evaluation is needed. Such biomarkers as soluble mesothelin-related protein and osteopontin provide some prognostic information, though with limitations. The baseline serum neutrophil-to-lymphocyte ratio could also provide prognostic information. Modern metabolic imaging techniques, for example PET/CT, can indicate prognosis by use of baseline total glycolytic volumes (TGV). TGV may also be useful in identifying early responders to systemic chemotherapy treatment. Research to identify clinically useful prognostic factors in MPM remains a priority.